Insights on Socio-Economic Structure, Culture, Religious Beliefs, Philosophy, Mythology, Custom Astrology and Traditions Practices of Lothal Town. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Lothal, a prominent city of the Indus Valley Civilization (IVC), provides valuable insights into the social, cultural, and religious aspects of this ancient civilization. While direct evidence like written texts is still undeciphered, archaeological findings at Lothal and other Harappan sites allow us to infer a great deal. Understanding the religious, philosophical, and mythological aspects of Lothal, like the broader Indus Valley Civilization (IVC)